Ceasing vitamin D replacement in infants with premature closure of front fontanelle: True or false? - Ünüvar, Tolga; Uygur Şahin, Türkan; Adal, Erdal (Galenos Yayıncılık, 2020)
Objective: The purpose of this study was to determine whether fontanelle closure in neonatal and early infantry periods was related to vitamin D levels and the prophylaxis of vitamin D intake. Moreover, our analysis was structured in a retrospective, controlled manner to evaluate our hypothesis.Materials and Methods: We considered 50 individuals who applied to our child endocrinology polyclinic with infants suffering from premature anterior closure. Further, 35 healthy infants of the same age and gender having open anterior fontanelles were taken as the control group.Results: The serum vitamin D level was found to be lower, and the parathormone level was significantly higher in the group with premature closure of the anterior fontanelle. In addition, there was a significant difference in serum calcium, alkaline phosphatase and parathormone levels in patients who had ceased vitamin D support compared with regular vitamin D users. While there was no significant difference in serum vitamin D levels, the level was lower in patients who had withdrawn vitamin D support.Conclusion: In our study, many infants have much lower vitamin D levels than normal levels, even though their anterior fontanelle is prematurely closed. Thus, physicians and other health workers are also warned of the continuity of vitamin D prophylaxis and that it is wrong to cease vitamin D support for reasons such as the premature closing of the anterior fontanelle.

Amaç: Biz çalışmamızda yenidoğan ve erken süt çocukluğu döneminde fontanel kapanmasının D vitamini düzeyi ve aldığı D vitamini profilaksisinin miktarı ile ilişkili olup olmadığını araştırmak istedik. Gereç ve Yöntemler: Çocuk endokrin polikliniğimize ön fon taneli 6. aydan erken kapanma şikayetiyle başvuran veya rutin muayene esnasında ön fontanelin 6.aydan önce kapandığı saptanan 50 hastanın çalışmaya alınması planlandı. Aynı yaş ve cinsiyetten ön fontaneli açık 35 sağlıklı çocuk kontrol grubu olarak alındı. Bulgular: Çalışmamızda, ön fontaneli erken kapanan grupta serum D vitamini düzeyi daha düşük saptanmasına karşın kontrol grubu ile arasında anlamlı bir fark saptanamadı. Serum parathormon düzeyi ise fontaneli erken kapanan hasta grubunda anlamlı olarak yükselmişti. D vitamini desteği kesilen hastalar ile düzenli D vitamini desteği alan hastalar karşılaştırıldığında serum kalsiyum, alkalen fosfataz ve parathormon düzeyleri arasında anlamlı fark saptandı. Serum D vitamini düzeyleri arasındaki fark anlamlı olmasa da D vitamini desteği kesilen hastalarda daha düşüktü. Sonuç: Çalışmamızda da gördüğümüz gibi ön fontaneli erken kapansa dahi vitamin D düzeyi normal hatta normalin altında birçok infant bulunmaktadır. Bu nedenle hem hekimlerin hem de diğer sağlık çalışanlarının D vitamini profilaksisinin devamlılığı konusunda uyarılması ve ön fontanel erken kapanması gibi sebeplerle D vitamini desteğinin kesilmesinin yanlış olduğu vurgulanmalıdır.
Ön fontaneli erken kapanan bebeklerde d vitamini replasmanının durdurulması: Doğru mu? Yanlış mı?
Keywords: Vitamin D; Anterior Fontanelle Closure; Child; D Vitamini; Ön Fontanel Kapanması; Çocuk